Ocorrência de helmintoses, de suínos criados na periferia de Itabuna - Bahia - Jaqueline Maria da Silva Pinto (2001)
This paper reports the results obtained from a helminth survey, with special emphasis for cysticercosis in 50 pigs (29 females and 21 males), breed, aged four to 18 months, weighing between 15 to 70kg, previous creations on the outskirts of the city of Itabuna, Bahia. The autopsy, identification of parasites and laboratory tests were done in the Campus of Universidade Estadual de Santa Cruz (UESC) during the months April to June 2001. The animals were killed with potassium chloride to 10%. The frequency of cysticercosis observed in 50 necropsy hurts 38%. We also identified the presence of 11 other species of helminths: Ascarops strongylina, Physocephalus sexalatus, Ascaris suum, Strongyloides ransomi, Macracantorhynchus hirudinaceus, Globocephalus urusubulatus, Oesophagostomum dentatum and O. longicaudum, Trichostrongyhus suis, and Metastrongyhus salmi Stephamurus dentatus.